Sonographic measurements can be misleading for diagnosing carpal tunnel syndrome in patients with rheumatoid arthritis - (:unkn) unknown (PUBLISAUDE-EDICOES MEDICAS LDA, 2016)
Objectives: To compare the nerve cross sectional areas (CSA) of patients with RA, without any sign of peripheral neuropathy, to healthy controls. Methods: Clinical, electrophysiological and sonographic assessments were done by three blinded researchers. The patients who had an electrodiagnostic or manifestations of peripheral neuropathy were excluded from the study. Nerve CSA were measured at various levels; hamatum hook, pisiforrn bone, radio-ulnar joint, distal 1/3 of forearm, and elbow for median nerve; radio-ulnar joint, pisiform bone, distal 1/3 of forearm, and medial epicondyle for ulnar nerve. Results: The study was completed with 30 women with RA and 30 healthy women. Despite both groups had neither clinical nor electrophysiological neuropathy, the sonographic measurements showed that median nerve CSA at radioulnar joint, pisifonn and hamatum levels of patients with RA were larger in rheumatoid arthritis patients than healthy controls. Ulnar nerve CSA at radioulnar joint, pisiform and distal 1/3 forearm and medial epicondyle levels of patients with RA were also increased (p<0.05). If the pisiform level median nerve CSA>10 mm(2) was used as sonographic carpal tunnel syndrome (CTS) criterion, 23/60 hands of 30 patients with RA and 5/60 hands of 30 healthy controls could be diagnosed as CTS. Conclusion: Median and ulnar nerve CSA were larger than healthy control in patients with rheumatoid arthritis, without clinical and electrophysiological peripheral neuropathy. The rheumatologists should be careful to diagnose CTS in patients with RA while using US.
Keywords: Rheumatoid arthritis; Ultrasonography; Peripheral; neuropathy; Electromyography; Carpal tunnel syndrome; NORMAL ULNAR NERVE; ULTRASONOGRAPHY; CONDUCTION; ULTRASOUND; SEVERITY